Peningkatkan Hasil Belajar Bahasa Indonesia Melalui Metode Role Playing - Eka Saputra, Erwin (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2024)
The problem in this classroom action research is that the low value of Indonesian through the role playing method can improve the speaking skills of Class V students at SDN 219 Ara, Bonto Bahari District, Bulukumba Regency. Bulukumba. The approach used is a qualitative approach. The type of research used is classroom action research which consists of two cycles, where each cycle consists of two meetings, with activity procedures including planning, implementation, observation and reflection. The subjects in this study were teachers and fifth grade students at SDN 219 Ara, Bonto Bahari District, Bulukumba Regency. Those who are actively registered in the odd semester of the 2012/2013 academic year have 10 students, consisting of 9 boys and 1 girl. Data collection techniques used are observation, tests and documentation. The data analysis technique used is descriptive quantitative analysis. The indicators of the success of this research are the indicators of the process and results of speaking skills. The results show that with the optimal application of the Role Playing method, student learning activities increase, this can be seen in the first cycle being in the medium category because it is seen from the results of the speaking skills test at the end of the first cycle where the average score The average student has not reached the predetermined KKM and in the second cycle is in the very high category. Thus there is an increase in students' speaking skills in Indonesian subjects after the implementation of the Role Playing method can increase.